PRIORITIES OF PENSION REFORM IN UKRAINE AT THE PRESENT STAGE - Rudyk , V.K. (The actual problems of regional economy development, 2017)
The issues of reforming the national pension system in modern conditions are considered. Their main elements, level of their using in the general pension model of the country are analyzed. The financial security of the pension sector, increasing in pension costs, tendencies of increase of their share relative to GDP for the future were assessed. Comparison of this indicator on the European countries was made. Priorities for pension reform were identified, main directions of reorganization of the solidarity pension system, the necessity of introduction of obligatory accumulative pension insurance were justified, the ways of further development of private pension provision were determined. Special attention was paid to the need to improve the legislative framework, which will be the legal basis for the successful conduction of this stage of the pension reform.